Love still stands [large type] - Irvin, Kelly (Irvin, Kelly. New Hope Amish., 2014)
Among a group of families leaving Bliss Creek to establish a new community in Missouri is Bethel Graber, a beautiful young woman with a passion for teaching. But after being disabled in a terrible accident, overseeing a classroom is out of the question. Bethel begins physical therapy, determined to make a fresh start. That won't be easy in the town of New Hope, where the locals seem anything but eager to welcome their new Amish neighbors.